Análisis a los estados financieros de la empresa “Mundihogar” ubicada en la ciudad de Zamora provincia de Zamora Chinchipe, correspondiente al periodo 2014 - 2015 - Remache Anguisaca, Martha Florencia (2017)
The thesis work titled; "ANALYSIS OF THE FINANCIAL STATEMENTS OF THE" MUNDIHOGAR "COMPANY LOCATED IN THE CITY OF ZAMORA PROVINCE OF ZAMORA CHINCHIPE, CORRESPONDING TO THE 2014-2015 PERIOD" It raises as a general objective: To carry out the analysis to the Financial Statements of the company "MUNDIHOGAR" located in The city of Zamora Province of Zamora Chinchipe, corresponding to the period 2014-2015. In order to measure the financial performance that allows achieving the fulfillment of the goals and objectives of the company. For the development of the work was necessary, the collection of information related to the subject of study, the review of analysis of the financial statements and internal policies of the company. In order to comply with the first objective, the vertical and horizontal analysis of the financial statements of the company "MUNDIHOGAR" was carried out in 2014 and 2015; to achieve this objective, a critical analysis of each of the accounts that comprise the financial statements and income statement was necessary. The vertical analysis on its part allowed determining the economic and financial structure, establishing the most significant accounts of assets, liabilities, Wealth, income, costs and expenses; And, the horizontal analysis allowed the comparison of the previous period with the current one and the behavior of each one of the balance sheet accounts. The second objective was to apply financial indicators to make appropriate decisions. The liquidity, activity, leverage and profitability indices were used to meet this objective in order to determine the financial and economic position of the company. Finally, the third objective was fulfilled. With the financial analysis and the application of reasons and indicators, the report was presented to the owner of the company, with the purpose of knowing the financial economic situation that maintains in his company and in this way can raise Policies to improve their sales level, allowing their better profitability. It is also recommended to implement the Financial Analysis report in order to improve your financial situation of the company.